PENERAPAN MODEL PROJECT-BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI PADA SISWA KELAS IV - Ni Wayan Karuni Arisa Putri; I Gede Sedana Suci; Putu Ayu Septiari Dewi; Ni Nyoman Ayu Suciartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Writing skills are one of the language competencies that need to be developed in elementary school students. However, many students still experience difficulties in developing ideas, arranging sentences coherently, and using appropriate vocabulary in descriptive text writing. This study aimed to describe the implementation of the Project-Based Learning (PjBL) model in improving descriptive text writing skills of fourth-grade students at SD Negeri 2 Tonja. This study employed a qualitative descriptive approach. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings showed that the implementation of Project-Based Learning was carried out through planning, implementation, presentation, and evaluation stages. Students became more active, enthusiastic, and collaborative during the learning process. In addition, students’ descriptive writing skills improved in terms of idea development, vocabulary selection, sentence arrangement, and paragraph coherence. Therefore, Project-Based Learning can be used as an effective learning model to improve descriptive text writing skills in elementary schools.